Controlled formation and characterization of dithiothreitol-conjugated gold nanoparticle clusters - Tsai, De-Hao (Langmuir : the ACS journal of surfaces and colloids, 2014)
We report a systematic study of the controlled formation of discrete-sized gold nanoparticle clusters (GNCs) by interaction with the reducing agent dithiothreitol (DTT). Asymmetric-flow field flow fractionation and electrospray differential mobility analysis were employed complementarily to determine the particle size distributions of DTT-conjugated GNCs (DTT-GNCs). Transmission electron microscopy was used to provide visualization of DTT-GNCs at different states of aggregation. Surface packing density of DTT and the corresponding molecular conformation on the Au surface were characterized by inductively coupled plasma mass spectrometry and X-ray photoelectron spectroscopy. Results show that DTT increases the aggregation rate of gold nanoparticles (AuNPs) up to ≈100 times. A mixed conformation (i.e., combining vertically aligned, horizontally aligned, and cross-linking modes) exists for DTT on the Au surface for all conditions examined. The primary size of AuNPs, concentration of DTT, and the starting concentration of AuNPs influence the degree of aggregation for DTT-GNCs, indicating that the collision frequency, energy barrier, and surface density of DTT are the key factors that control the aggregation rate. DTT-GNCs exhibit improved structural stability compared to the citrate-stabilized GNCs (i.e., unconjugated) following reaction with thiolated polyethylene glycol (SH-PEG), indicating that cross-linking and surface protection by DTT suppresses disaggregation normally induced by the steric repulsion of SH-PEG. This work describes a prototype methodology to form ligand-conjugated GNCs with high-quality and well-controlled material properties